NMT1 inhibition modulates breast cancer progression through stress-triggered JNK pathway. Issue 12 (December 2018) - Deng, Lu; Gao, Xinlei; Liu, Bingjie; He, Xueyan; Xu, Jiahui; Qiang, Jiankun; Wu, Qingfa; Liu, Suling
Abstract Myristoylation is one of key post-translational modifications that involved in signal transduction, cellular transformation and tumorigenesis. Increasing evidence demonstrates that targeting myristoylation might provide a new strategy for eliminating cancers. However, the underlying mechanisms are still yielded unclear. In this study, we demonstrated that genetic inhibition of N-myristoyltransferase NMT1 suppressed initiation, proliferation and invasion of breast cancer cells either in vitro or in vivo. We identified ROS could negatively regulate NMT1 expression and NMT1 knockdown conversely promoted oxidative stress, which formed a feedback loop. Furthermore, inhibition of NMT1 caused degraded proteins increase and ER stress, which cross-talked with mitochondria to produce more ROS. And both of oxidative stress and ER stress could activate JNK pathway, leading to autophagy which abrogated breast cancer progression especially triple-negative breast cancer (TNBC). These studies provide a preclinical proof of concept for targeting NMT1 as a strategy to treat breast cancer.